The use of computer simulation to improve road safety at the intersection of Volgogradskaya and Korolenko Streets in Kazan, Republic of Tatarstan - Ramil R. Zagidullin; Ivan A. Bannikov (International Journal of Advanced Studies, 2025)
A traffic accident is a phenomenon that has already become an integral part of human life, and although it is often taken for granted, accidents have serious consequences for people, resulting in physical injury, emotional stress, financial loss, and death. In addition, accidents can cause traffic jams, which leads to delays, creating inconveniences for movement.